Developing Podcasts as a Learning Medium in the Digital Era for Business Administration Students as the Vocational Faculty of Brawijaya University - Hapsari Dian Sylvatri; Citra Dewi Megawati (Baca Dulu Publisher, 2025)
This research explores the development of podcasts as an innovative digital learning medium for Business Administration students at the Vocational Faculty, Universitas Brawijaya. The study aims to enhance students' technological competence (TKT), specifically at level 4, by using podcasts as alternative learning media. By employing a qualitative descriptive research method, the data were gathered through questionnaires distributed to students, focusing on their perceptions of podcast use in learning. The findings suggest that podcasts are effective in increasing students' understanding, interest, and involvement in learning, and contribute positively to their readiness for the digital era. Podcasts offer flexibility, accessibility, and cater to diverse learning styles, making them an ideal supplement to traditional learning tools.